DAMPAK POSITIF PENGGUNAAN MEDIA SOSIAL (TIKTOK) SEBAGAI SARANA PEMBELAJARAN TAJWID DAN TAHSIN ALQURAN - Febry Amirullah Benny; Rizqi Nailul Baroroh; Rabiatul Adawiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Al Qur’an as a guide to life for Muslims requires in-depth understanding and proper practice. In the digital era, social media such as Tiktok has become a popular platform that can be used as a means of learning recitation and tahsin. This research aims to analyze the impact of using social media Tiktok on learning recitation and tahsin of the Qur’an. The research method used is descriptive qualitative with data collection techniques in the form of library research. The results of research using library research show that the use of social media Tiktok has a positive influence on learning recitation and tahsin of the Qur’an. In various literature, it is stated that students as TikTok users benefit and are helped in understanding Tajwid and Tahsin material. Students find it easier to memorize and practice, and are motivated to learn further. The results of this study show that TikTok can be used as an alternative media in learning recitation and tahsin of the Qur'an.